Determining the dynamics of carbon monoxide formation during gas welding processes - Viacheslav Berezutskyi (PC Technology Center, 2021)
This paper reports a study of the air medium where welding processes take place, with special attention paid to the evolution of carbon monoxide (CO) in the working medium in the process of gas welding. Plots were constructed and polynomial dependences were obtained to show a change in the concentration of carbon monoxide in the air of the working area during gas welding.